Protein Tyrosine Phosphatase 1B (PTP1B) and \(α\)-Glucosidase (3W37) Inhibitors from Tetradium ruticarpum: In vitro and In silico Study - To, Dao-Cuong; Nguyen, Phi-Hung; Tran, Manh Hung (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
Folk experiences suggest natural products in Tetradium ruticarpum can be effective inhibitors towards diabetes-related enzymes. This study evaluated the inhibition effects on protein tyrosine phosphatase 1B (PTP1B) and \(α\)-glucosidase (3W37) of isolated compounds from T. ruticarpum as well as using density functional theory and molecular docking techniques as computational methods to predict the stability of the ligands and simulate the interaction between the studied inhibitory agents and the targeted proteins. The results showed that two natural products: schinifoline (1) and intergrifoliodiol (2) were isolated from the buds of T. ruticarpum. These compounds (1 and 2) possess high potentiality for the inhibition of PTP1B (IC50 values of 24.3 ± 0.8, and 47.7 ± 1.1 \(μ\)M) and \(α\)-glucosidase (IC50 values of 92.1 ± 0.8, and 167.4 ± 0.4 \(μ\)M) in vitro. Docking score (DS) values and the number of interactions obtained from docking simulation highly correlate with the experimental results yielded. Furthermore, detailed investigations of the structure-activity relationship reveal that the amino acids Arg254 and Arg676 play a substantial role in the overall conformational distortion of PTP1B and 3W37 structures, resulting in the loss of enzymatic activity reported in assay-based experiments. This research calls for more research, either to produce better diabetic treatments or to confirm the role of the amino acids Arg254 and Arg676.